INTERNATIONAL VOLUNTEERING AS A RESOURCE OF RUSSIAN UNIVERSITIES - Maria V. Pevnaya; Anastasiya N. Kalinina (Высшее образование в России)
The article highlights the role of international volunteering in the development of universities, examines the social capital of international volunteers from Russian universities. Due to the analysis of the survey among the students of the leading Russian universities (N=930; 2015) we have found the significant factors and distinctive features of the Russian students experienced in international volunteering. The evaluation of cultural, social, economic resources is provided.